Efek Fraksi n-Heksana Kulit Hylocereus polyrhizus TerhadapAktivitas Katalase Tikus Stres Oksidatif - Untari, Eka Kartika; Wahdaningsih, Sri; Damayanti, Agustia (Pharmaceutical Sciences and Research, 2014)
Production of excess free radicals cause oxidative damage and degenerative diseases. Catalase enzyme is one of the endogenous intracellular antioxidant that can be reduced by oxidative stress conditions. The peel of red dragon fruit (Hylocereus polyrhizus) as a potent exogenous antioxidants could support the internal enzyme activity to prevent free radicals. The aim of this research was to determine the effect of n-hexane fraction of H.polyrhizus’s peel and the dose that could increase activity of catalase. The peel was maserated with chloroform, then fractionated by n-hexane. Stress condition was achieved by five days fasting and swimming for 10 mins/day to test animals. UV-Vis spectrophotometer was used to measure the activity of catalase. The rats were divided into 6 groups: normal control, negative control, dose I (10 mg/200 gBB), dose II (40 mg/200 gBB), positive control quercetin as (4 mg/200 gBB) and vitamin E (17.64 mg/kg). The activity of catalase enzyme in the normal control is 29.4 units/ml; negative control is 7.08 units/ml; dose I is 14.42 units/ml; dose II is 14.79 units/ml’quercetin is 28.18 units/ml; and vitamin E is 71.29 units/ml. Our conclusion is the activity of the catalase enzyme rat under oxidative stress can be increased by the n-hexane fraction of H. polyrhizus.